Estimativa empírica de funções de engel: o caso da alimentação em Viçosa - Monteiro da Silva , Orlando; Dias Casali , Albino Sergio (Revista Ceres, 2025)
The objective of the present study was to analyze statistically and economically the empirical fit of the Engel relationship to consumer income and food purchases.